Optimalisasi Kecepatan Kendaraan Angkutan Sampah di Kota Manado - Kumaat, Meike; Lefrandt, Lucia (Universitas Negeri Gorontalo, 2025)
Waste management is a problem in all regions in Indonesia, including the city of Manado. Delays in waste transportation can cause odor problems and accumulation of waste that will disturb the surrounding environment. A good waste transportation system is needed, especially for the city of Manado, which is effective and efficient. The efficiency reviewed is in terms of Vehicle Operating Costs (BOK), so that it can be known exactly the BOK per kilometer of the garbage truck for each route reviewed.The BOK analysis uses PCI analysis to calculate the BOK per kilometer for dumptruck vehicles. The route taken by the garbage trucks operating in Malalayang Sub-district has 2 villages, namely Malalayang 1 West Village and Malalayang 1 Village. The first ritation of the truck goes to Wolter Monginsidi Street, transports garbage along the protocol road and returns to Sumompo Landfill. The second ritation of garbage trucks will go to the Intermediate Transfer Station (SPA) in Malalayang 1 Barat and Malalayang 1 villages to wait for garbage carts that transport door to door and then return to the Sumompo landfill. The results of the BOK research for trucks operating in Malalayang 1 West Village amounted to Rp. 292,463 for one day of operation. While the BOK for garbage trucks operating in Malalayang 1 Village is Rp. 283,526 for one day of operation